The Effectiveness of Sound Stimulators as a Means of Monitoring Fetal Well-Being at the Gatot Soebroto Army Central Hospital - H.R., Teni Nurlatifah; Rhismayati, May; Wijayanegara, Hidayat (Jurnal Bidan Cerdas, 2025)
Introduction: Fetal inactivity during well-being monitoring can stem from sleep rather than distress. This study assessed a sound stimulator, a vibroacoustic device using digital speaker-emitted sound waves, against the traditional klenengan bell for awakening sleeping fetuses. Objective: The aim was to assess the stimulator's effectiveness in awakening sleeping fetuses and to verify its proper usage by operators. Methods: The intervention group received the sound stimulator, emitting a consistent decibel level (10-68 dB) via a speaker placed near the fetal head for approximately one minute. A quantitative, posttest-only study design was employed at Gatot Soebroto Army Central Hospital, involving 60 participants. Ethical approval was granted by the Institute of Health Research Ethics Committee of Dharma Husada College of Health Sciences (No. 13/KEPK/SDHB/B/V/2023). Results: The sound stimulator successfully awakened 27 of 30 sleeping fetuses within 30 seconds. Device suitability was high, with 29 of 30 deemed appropriate and 27 achieving noise levels below 68 dB, prioritizing safety and comfort. Conclusion: Wilcoxon Signed Rank test results (Asymp.sig = 0.035) confirmed the stimulator's effectiveness. The innovative sound stimulator was superior to the klenengan bell. It provides a practical, efficient, and safe tool (noise levels <68 dB) for fetal welfare monitoring